Enhancing the Incident Response Capabilities of the UAE Critical Infrastructure Against Phishing Cyber Security Threat: An AI-Based Approach - Bushra Rwashdeh (2025)
Phishing attacks pose a significant threat to critical infrastructure in the UAE. This study proposes an AI-driven approach to enhance incident response capabilities against such threats. The research adapts the Technology Threat Avoidance Theory (TTAT) to an organizational context and develops a machine learning model for phishing detection and response. This research contributes to both theory and practice by extending TTAT and creating an AI prototype tailored to the UAE's critical infrastructure needs. The study employs a design science approach, incorporating qualitative evaluations from UAE experts to refine the model. This research aims to strengthen organizational resilience and contribute to the UAE's national cybersecurity objectives.